Combined oral prolonged-release oxycodone and naloxone in opioid-induced bowel dysfunction: review of efficacy and safety data in the treatment of patients experiencing chronic pain - Clemens, Katri Elina; Mikus, Gerd (Expert opinion on pharmacotherapy, 2010)
IMPORTANCE OF THE FIELD: Despite proven analgesic efficacy, opioid use is associated with frequently dose-limiting bowel dysfunction that seriously impacts patients' quality of life (QoL). Agents used at present to manage opioid-induced constipation do not address the underlying opioid receptor-mediated cause of bowel dysfunction and are often ineffective. There is, therefore, a significant need for more effective treatment options. The combination of the strong opioid oxycodone and the opioid antagonist naloxone has the potential to prevent opioid-induced bowel dysfunction (OIBD) while maintaining analgesic efficacy. - OBJECTIVE: To review the safety and efficacy of oral prolonged-release (PR) oxycodone/naloxone in the treatment of patients experiencing chronic pain. - AREAS COVERED IN THIS REVIEW: A MEDLINE search was done (January 2002 - July 2009) for available literature for prolonged release oxycodone and naloxone in different patient groups. Results were limited to English-language and clinical trials. Data were also obtained from congress materials. WHAT KNOWLEDGE THE READER WILL GAIN: Unmet needs of opioid pain treatment in terms of OIBD, reduced QoL and low treatment compliance, leading to reduced efficacy. A data overview demonstrates the efficacy and tolerability of PR oxycodone/naloxone in the management of severe chronic pain without the burden of severe gastrointestinal adverse events. The combined formulation of a highly effective opioid and an antagonist that acts locally to reduce gastrointestinal side effects is expected to simplify pain management. - TAKE HOME MESSAGE: The combination of PR oxycodone/naloxone offers the potential of maintaining normal bowel function in patients requiring opioid therapy--it is a strong analgesic that is well tolerated.